Perfil axiológico para el desarrollo de competencias ciudadanas (2018)
Citizenship education, axiological training and study plans are understood as the means by which the habits, customs and values of a community are transferred from one generation to the next generation. Education is developed through situations and experiences lived by each individual throughout their lives. In this order of ideas in the present work is aimed at designing teaching strategies that support student training from an axiological profile for the development of citizenship skills. To this end, the personal, social and school dimensions of the student are addressed and the conception of citizenship competences is analyzed in the curriculum. The research design is documentary and field; We work with students from San Andres Island. Among the main results we state that the disruptive behaviors generated in the classroom affect the development of citizenship skills and are directly associated with the students' values training. It concludes in the need to define strategies that are oriented to the development of citizen competences giving priority to the axiological profile of the students.